Agribusinesses, smallholder tenure security, and plot-level investments: Evidence from rural Tanzania - Kacana Sipangule (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
The last decade has witnessed an increase in the interest in agricultural land in developing countries. While a great deal of attention has been paid to understanding the impacts of this increased interest in agricultural land, very little is known about how local smallholder communities are affected when agribusinesses decrease or cease their operations. A large number of agribusinesses that acquired agricultural land in many sub-Saharan African countries have reduced or ceased their operations in recent years. This paper introduces a new dimension to the literature by investigating how a decrease in the share of land held by an agribusiness in a village affects smallholder plot-level tenure security and investments in rural Tanzanian villages. Drawing on a panel of 5,101 plots, we find that a decrease in the share of land held by an agribusiness significantly increases the probability that a plot has tenure security. Moreover, our results reveal that a decrease in the share of land held by agribusinesses significantly raises the time spent on the plot. This result is primarily driven by the number of household members employed in the agricultural sector but not through changes in tenure security.
Keywords: Q12; Q13; Q1; 330; tenure security; smallholders; agribusiness; Tanzania; property rights